Is nasogastric suction necessary in acute pancreatitis?. Issue 6138 (2nd September 1978) - Naeije, R; Salingret, E; Clumeck, N; De Troyer, A; Devis, G
Abstract : Fifty-eight patients with mild to moderately severe acute pancreatitis were randomly allocated to treatment with or without nasogastric suction (27 and 31 patients respectively). Intravenous fluids and pethidine hydrochloride were also given. The two groups were comparable clinically at the start of the study. There were no differences between the two groups in the mean duration of the following features: abdominal pain or tenderness; absence of bowel movements; raised serum amylase concentration; time to resumption of oral feeding; and days in hospital. Prolonged hyperamylasaemia (serum amylase greater than 0.33 mU/l) occurred in one patient in the suction group and in three patients in the non-suction group. A mild recurrence of abdominal pain after resumption of oral feeding occurred in three patients in the suction group and in two patients in the non-suction group. Two patients in the suction group developed overt consumption coagulopathy and two others pulmonary complications. No patient in the non-suction group had complications. The findings suggest that most patients with mild to moderately severe acute pancreatitis do not benefit from nasogastric suction. The procedure should be elective rather than mandatory in treating this condition.